Metamorphoses in the discourse and the rise of the new homo politicus before the 2018 elections - de Oliviera, Rafael Camargo (2020)
This work has as objective to analyze the constructions made of the political subject in the present time or, as we chose to use in the course of the text, the new homo politicus. The concept was used by Jean-Jacques Courtine in his article ‘The metamorphoses of homo politicus’, published in Brazil in Legados de Pêcheux: inéditos em análise do discurso (PIOVEZANI; SARGENTINI, 2011). In order to carry out the studies, we use the notions of enunciation, discourse, knowledge and power consolidated by the French philosopher M. Foucault. Thus, this research is inserted in the studies of the Foucaultian discourse and is used of archeology and genealogy for the construction of the method of analysis. As a theoretical contribution, the works used were: Archeology of knowledge (2012), Discipline & Punish (2011), History of sexuality I (1988) and The birth of biopolitics (2008).